THE ROLE OF HIGHER EDUCATION IN SUPPORTING SUSTAINABLE DEVELOPMENT IN THE TROPICAL RAINFOREST REGION - Ratna Wati; Jawatir Pardosi; Warman; Sri Wahyuni; Desi Iska Fadilah; Andi Sirajuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Tropical rainforest regions, exemplified by the island of Borneo and the Indonesian province of East Kalimantan, sit at the intersection of accelerating environmental change and rapid economic transformation. Between 1973 and 2010, Borneo lost roughly 30% of its 1973 forest cover, and national monitoring data indicate that Indonesian deforestation surged again in 2025, reversing several years of decline. Higher education institutions (HEIs) are increasingly recognised as pivotal actors in reconciling ecological protection with development, through their three-fold mandate of education, research, and community service. This article examines how HEIs situated in and around tropical rainforest regions, using East Kalimantan as an illustrative case, contribute to sustainable development through curriculum integration, applied research on forest and community systems, and structured community engagement that incorporates indigenous ecological knowledge. Drawing on an integrative review of peer-reviewed literature, institutional reports, and policy documentation, the article synthesises the mechanisms, opportunities, and constraints that shape the sustainability contribution of HEIs in this setting, with particular attention to the pressures and opportunities created by the relocation of Indonesia's national capital (Ibu Kota Nusantara, IKN) to East Kalimantan. The findings indicate that HEIs contribute most effectively to sustainable development when the three pillars of the Tri Dharma Perguruan Tinggi are deliberately integrated rather than pursued separately, and when community-engagement programmes are co-designed with local and indigenous communities rather than delivered to them. The article concludes with practical recommendations for strengthening the sustainability role of HEIs operating in tropical rainforest regions